VARIABILITY ANALYSIS AND MULTIVARIATE ANALYSIS IN BREAD WHEAT [TRITICUM AESTIVUM L.] - SIDDHI SHAH,; D. R. MEHTA,; LATA RAVAL, (The Bioscan, 2015)
Genetic variability and diversity was done with 52 genotypes for fourteen quantitative characters in bread wheat (Triticum aestivum L.). The analysis of variance indicated the sufficient genetic variation among the genotypes for all the traits. High genotypic coefficient of variation (GCV) coupled with high heritability and high genetic advance as per cent of mean (GA %) were observed for days to 50% flowering (9.13%, 78.97%, 16.71%) , days to maturity (5.45%, 87.73%, 10.52%) plant height (7.60%, 73.32%, 13.41%), number of grains per main spike (9.89%, 78.31%, 18.02%), grain yield per plant (10.12%, 50.18%,14.76%) and biological yield per plant (7.03%, 59.50%, 11.16%) which might be attributed to additive gene action and phenotypic selection could be effective for these traits. On the basis of Multivariate analysis, 52 genotypes grouped in seven clusters using the Tocher’s method. Cluster I topped with maximum (38) genotypes followed by cluster II (5) and cluster III (4), while cluster V to VII were solitary clusters. Maximum genetic distance (D) was found between cluster II and III (15.23). Days to maturity, days to 50% flowering and 100-grain weight also contributed more than 55% of towards total genetic divergence.